Intrapreneurship in learning organizations: moderating role of organizational factors - Alipour, Farhad; Idris, Khairuddin; Karimi, Roohangiz (Marsland Press, 2011)
The aim of this paper is to investigate moderating effect of organizational factors in the relationship between learning organization and intrapreneurship. In line of this objective it theoretically explores the nature of intrapreneurship dimensions, the nature of learning organization dimensions, how learning organization can be linked to intrapreneurship, and how organizational factors influence the relationship between learning organization and intrapreneurship. This study would help researchers, practitioners and managers to have a better understanding on the relationship between learning organization and intrapreneurship and the role of organizational factors.